MODIFIED WATERSHED ALGORITHM BASED ON DISTANCE- METRIC CRITERION FOR NUCLEI CLUSTERED SEPARATION IN PAP SMEAR IMAGES - Rahadian Kurniawan (Faculty of Industrial Technology Universitas Islam Indonesia, 2013)
An improved watershed algorithm based on distance-metric criteria to separate overlapping cells proposed in this study. In this study, we present a novel watershed-based method for separation of overlapping cervical cell in Pap smear images. The results will be compared with other method namely distance transform, and color morphology gradient. The result of proposed method shows not only produces accurate separating cells cluster, but also keeps the shape of cells in good form.